Sixteen isostructural phosphonate metal-organic frameworks with controlled Lewis acidity and chemical stability for asymmetric catalysis - Xu Chen (Nature Portfolio, 2017)
Asymmetric synthesis predominantly falls within the realm of homogeneous catalysis. Here, the authors synthesized 16 chiral metal–organic frameworks differing in the nature of the transition metal and demonstrate their excellent stability, catalytic activity and recyclability in a number of enantioselective reactions.